(3GdEYdGe aj hajGJ GdCYdGes - (3ESeGYjd Hf eMeO Hf HQOS GdHYdHcj, YeGO GdOjf CHh GdaOGA, GHf HQOS , J (B786 (3g` s; (3GdPgHj,J (B748 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG fXQJ ai cJGH GdJPcQI ai WHbGJ GdMaGX ddYOd GdMGaX TeS GdOjf CHj YHO Gddg GdPgHi s
(3BNQgG (B:s
(3Ydi GdfHi GdgGTei GdYQHi eMeO NjQ GdGfGe GdWjH hBdg hUMHg Ggd GdhaG hRGOge QH GdeYGdi TQakG s
(3hgj efXheI ai haGI GdMaGX GdPjf PcQge GdMGaX TeS GdOjf GdPgHi HMQha GdLeds
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B23 s
Keywords: (3GdJGQjNs